An Enhanced Mobile Device Based Navigation Model: Ubiquitous Computing - Olajubu, Emmanuel; efiong, john E (﻿IGI ﻿Global, 2023)
TITLE:An Enhanced Mobile Device Based Navigation Model: Ubiquitous Computing VOLUME NO:9 ISSUE NO:2 JANUARY TO MARCH 2018 PAGES:23